Open Government Partnership: Indonesian Transformative Effort to Deal with Corruption - Zakia Syifa (Universitas Airlangga, 2017)
This research seeks to explain the underlying reasons of why Indonesia under Yudhoyono administration joined Open Government Partnership (OGP). Based on the relationship between democracy, corruption, and good governance, this research explores on how corruption had caused negative impacts not only to domestic sphere, but also to Indonesia’s international legitimacy which leads to affect the economic growth. Focusing on the process of the OGP initiation, the scope spans from July 2010, when Indonesia was first invited to join this initiative, to September 20, 2011, when Indonesia became one of the eight founding countries to launch OGP in New York. This research suggests that Indonesia joined OGP to help ease the negative impacts of corruption. From the research, there are findings that corruption had caused negative implications in domestic sphere and international legitimacy, which leads to curb Indonesia’s potential investment and economic growth.